Comprehensive Analysis of the Structure and Allergenicity Changes of Seafood Allergens Induced by Non-Thermal Processing: A Review - Fengqi Wang; Hangyu Zhong; Jun-Hu Cheng (Molecules, 2022)
Seafood allergy, mainly induced by fish, shrimp, crab, and shellfish, is a food safety problem worldwide. The non-thermal processing technology provides a new method in reducing seafood allergenicity. Based on the structural and antigenic properties of allergenic proteins, this review introduces current methods for a comprehensive analysis of the allergenicity changes of seafood allergens induced by non-thermal processing. The IgE-binding capacities/immunoreactivity of seafood allergens are reduced by the loss of conformation during non-thermal processing. Concretely, the destruction of native structure includes degradation, aggregation, uncoiling, unfolding, folding, and exposure, leading to masking of the epitopes. Moreover, most studies rely on IgE-mediated assays to evaluate the allergenic potential of seafood protein. This is not convincing enough to assess the effect of novel food processing techniques. Thus, further studies must be conducted with functional assays, in vivo assays, animal trials, simulated digestion, and intestinal microflora to strengthen the evidence. It also enables us to better identify the effects of non-thermal processing treatment, which would help further analyze its mechanism.